2014
DOI: 10.1126/science.1254917
|View full text |Cite
|
Sign up to set email alerts
|

Poly-dipeptides encoded by the C9orf72 repeats bind nucleoli, impede RNA biogenesis, and kill cells

Abstract: Many RNA regulatory proteins controlling pre-mRNA splicing contain serine:arginine (SR) repeats. Here we found that these SR domains bound hydrogel droplets composed of fibrous polymers of the low-complexity domain of heterogeneous ribonucleoprotein A2 (hnRNPA2). Hydrogel binding was reversed upon phosphorylation of the SR domain by CDC2-like kinases 1 and 2 (CLK1/2). Mutated variants of the SR domains changing serine to glycine (SR-to-GR variants) also bound to hnRNPA2 hydrogels, but were not affected by CLK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
714
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(762 citation statements)
references
References 35 publications
44
714
3
1
Order By: Relevance
“…Furthermore, we recently showed that ALS astrocytes, including mutFUS expressing patient astrocytes, drive up‐regulation of the multidrug resistance transporter P‐Glycoprotein (P‐gp) in endothelial cells of the blood‐brain barrier (Qosa et al, 2016). Astrocytes participate in disease also through a “loss of function” [reviewed (Maragakis and Rothstein, 2006)] as demonstrated by several human and rodent studies that have observed defects and/or loss of astrocytic glutamate transporter EAAT2/GLT1 for several ALS subtypes including SOD1‐ALS (Benkler, Ben‐Zur, Barhum, & Offen, 2013; Howland et al, 2002) sALS (Lin et al, 1998), and C9orf72‐ALS (Kwon et al, 2014). In contrast, studies of astrocytic contributions in TDP‐43‐mediated ALS have shown conflicting results for both gain and loss‐of‐function toxicity (Haidet‐Phillips et al, 2013; Serio et al, 2013; Tong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we recently showed that ALS astrocytes, including mutFUS expressing patient astrocytes, drive up‐regulation of the multidrug resistance transporter P‐Glycoprotein (P‐gp) in endothelial cells of the blood‐brain barrier (Qosa et al, 2016). Astrocytes participate in disease also through a “loss of function” [reviewed (Maragakis and Rothstein, 2006)] as demonstrated by several human and rodent studies that have observed defects and/or loss of astrocytic glutamate transporter EAAT2/GLT1 for several ALS subtypes including SOD1‐ALS (Benkler, Ben‐Zur, Barhum, & Offen, 2013; Howland et al, 2002) sALS (Lin et al, 1998), and C9orf72‐ALS (Kwon et al, 2014). In contrast, studies of astrocytic contributions in TDP‐43‐mediated ALS have shown conflicting results for both gain and loss‐of‐function toxicity (Haidet‐Phillips et al, 2013; Serio et al, 2013; Tong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, depletion of various RPs, including S6 or S14, disrupts ribosomal biogenesis without interfering with nucleolar integrity (4). Impaired ribosome production and/or ribosomal deficits are documented in various neurodegenerative diseases, including Alzheimer, Huntington, Parkinson, amyotrophic lateral sclerosis (ALS), and fronto-temporal lobe dementia (FTLD) (5)(6)(7)(8)(9)(10)(11)(12)(13). Reduced ribosomal biogenesis may also contribute to neurodevelopmental disorders.…”
mentioning
confidence: 99%
“…A gain of toxic function hypothesis is also supported by the presence of repeat-associated non-ATG dependent translation (RAN translation) to generate dipeptide repeats (DPRs), which have been detected in C9orf72-ALS/FTD tissue [18,23]. It is known that RAN translation of the intronic GGGGCC C9orf72 repeat expansions in both sense and anti-sense directions can generate up to five different DPRs, which can be toxic [18,[23][24][25][26].…”
Section: Amyotrophic Lateral Sclerosis (Als) Also Commonly Known Asmentioning
confidence: 95%